2004
DOI: 10.1111/j.1365-2125.2004.02220.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication reviews in the community: results of a randomized, controlled effectiveness trial

Abstract: Br J Clin PharmacolBritish Journal of Clinical Pharmacology DOI:10.1111DOI:10. /j.1365DOI:10. -2125DOI:10. .2004 AimsTo examine the effectiveness of a multidisciplinary service model delivering medication review to patients at risk of medication misadventure in the community. MethodsThe study was carried out in three Australian states; Queensland, New South Wales and Western Australia, and conducted as a randomized, controlled effectiveness trial with the general practitioner (GP) as the unit of randomization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
231
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(247 citation statements)
references
References 41 publications
(60 reference statements)
9
231
3
4
Order By: Relevance
“…1 Source: http://www.medicareaustralia.gov.au/provider/pbs/fourth-agreement/hmr.jsp 2 Source: http://www.guild.org.au/mmr/content.asp?id=53 3 Patients who have had an HMR in the recent past 4 Patients who have never had an HMR but would qualify for this service according to the Australian Government's eligibility criteria and risk factors 5 This paper does not include the Aboriginal and Torres Strait Islander and ethnic consumer groups. Due to their distinctly different circumstances, the attitudes of these consumer segments are discussed in a separate paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Source: http://www.medicareaustralia.gov.au/provider/pbs/fourth-agreement/hmr.jsp 2 Source: http://www.guild.org.au/mmr/content.asp?id=53 3 Patients who have had an HMR in the recent past 4 Patients who have never had an HMR but would qualify for this service according to the Australian Government's eligibility criteria and risk factors 5 This paper does not include the Aboriginal and Torres Strait Islander and ethnic consumer groups. Due to their distinctly different circumstances, the attitudes of these consumer segments are discussed in a separate paper.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] It is therefore in the public interest that this cognitive pharmacy service is effectively used by patients who are at highest risk of medication misadventure. However, recent research confirmed that those in greatest need of an HMR are the least likely to receive this service.…”
Section: Introductionmentioning
confidence: 99%
“…MedsChecks, Diabetes MedsChecks and Clinical Interventions by pharmacists), none of which is supported by any evidence in the context of the Australian healthcare setting. Conversely, there is evidence on the value of HMRs to consumers, 2,5,6 a demonstration of cost savings of up to $550 per HMR to the health system, 7-10 and a demonstrable track record that clearly illustrates the delivery of a truly collaborative service between GPs, patients, independent accredited pharmacists and other community or hospitalbased pharmacists [11][12][13][14][15][16][17][18] (Fig. 1).…”
mentioning
confidence: 99%
“…Australian studies have demonstrated that HMRs can resolve, manage or reduce medicine-related problems for a wide range of patients. [11][12][13][14][15][16][17][18][19][20][21] In addition, HMRs improve health outcomes; for example, in patients receiving betablockers for heart failure, an HMR resulted in a 45% reduction in likelihood of hospitalisation for heart failure at any time. 18 Another study found that an HMR in patients taking warfarin resulted in a 79% reduced likelihood of bleeding-associated hospitalisation 2-6 months after the HMR.…”
mentioning
confidence: 99%
See 1 more Smart Citation